2018
DOI: 10.22610/jevr.v9i1.2557
|View full text |Cite
|
Sign up to set email alerts
|

Implementation Interactive Media and Characterized Meme Media: A Comparation Study

Abstract: This study aimed to determine the effectiveness of the implementation of interactive media and characterized meme media on the student learning. This study applied experimental research method which used simple random sampling technique. The participants of the study consisted of two group as group A amount twenty-nine students and group B amount twenty-eight students. Each group had a different treatment, for the group a was treated by implementing interactive media, while group B was treated by implementing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 6 publications
0
4
0
3
Order By: Relevance
“…Although memes are not a traditional form of art such as painting or drawing, they are simple to make through online meme-generator websites, show creativity and humor, and can be widely disseminated. 13,17 As such, memes could be considered as a creative arts outlet, although further research is needed to understand its effect on burnout and resiliency.…”
Section: Discussionmentioning
confidence: 99%
“…Although memes are not a traditional form of art such as painting or drawing, they are simple to make through online meme-generator websites, show creativity and humor, and can be widely disseminated. 13,17 As such, memes could be considered as a creative arts outlet, although further research is needed to understand its effect on burnout and resiliency.…”
Section: Discussionmentioning
confidence: 99%
“…The media needs that respondents want other than the MCH Handbook are interactive learning media. Research on the implementation of learning media found that the use of interactive learning media (audiovisual) was more effective in improving learning outcomes than print media (35).…”
Section: The Next Materials Respondents Need Ismentioning
confidence: 99%
“…Hal ini dapat dilihat dalam penyampaian materi teori dan praktek seorang guru mengusahakan menggunakan media yang beragam. Media pembelajaran dapat digolongkan dalam beberapa macam, akan tetapi pada intinya media dapat di golongkan menjadi media audio, media visual dan media gabungan dari keduanya (Sumarsono & Sianturi, 2018).…”
Section: Pendahuluanunclassified